(untitled) (Research, Society and Development, 2022)
Despite not being part of a routine in most schools, school hearing screening (TAE) is extremely important, as it evaluates individuals in the school environment, those students who already have hearing impairment or who may have developed it due to some pathology. This study aims to carry out a survey of the scientific literature regarding school hearing screening and its importance. This is an integrative literature review, carried out from January to February 2022. The search strategies allowed the identification of 214 articles in the Lilacs and SciELO databases. During the analysis of titles and abstracts, applying the inclusion criteria, 203 articles were excluded. In total, 12 were selected because they met all the requirements. The results emphasize the importance and benefits that School Hearing Screening (TEA) offers to the child in the school phase, offering greater attention in the detection of possible alterations, giving the proper guidance and prevention, thus being able to contribute to the diagnosis and the early intervention for hearing loss. Therefore, it is concluded that, despite not being mandatory by law, school hearing screening is of paramount importance for monitoring hearing health and helping early intervention, so that in this way it can improve the quality of life of the individual and their school performance.